International human resource management : policies and practices for multinational enterprises - Tarique, Ibraiz; Briscoe, Dennis R., 1945-; Schuler, Randall S. (Global HRM, 2022)
The updated sixth edition of International Human Resource Management is an authoritative resource that focuses on international human resource management (IHRM) within multinational enterprises (MNEs). The book includes fifteen chapters with rich pedagogy students have come to expect and is organized into four sections: Strategic Context National and Cultural Context Global Talent Management Role and the Future of IHRM Each chapter has been designed to lead readers through key topics in a highly engaging and approachable way with learning goals, relevant data, exhibits, figures, vignettes, end-of-chapter case studies, discussion questions, up-to-date content, and numerous references. The sixth edition includes discussions on evolving IHRM topics such as international experiences and adult third culture kids, expanded analyses on health and safety statistics and global workforce analytics, as well as updated and revised illustrations, cases, references and instructor resources. Uncovering precisely why IHRM is essential for success in international business and how IHRM policies and practices function within the multinational enterprise, this comprehensive textbook provides an excellent foundation for understanding the theory and practice of IHRM. It is essential reading for all students, instructors, and IHRM professionals.